2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037236
|View full text |Cite
|
Sign up to set email alerts
|

An IC-based controllable stimulator for respiratory muscle stimulation investigations

Abstract: Functional Electrical Stimulation can be used to restore motor functions loss consecutive to spinal cord injury, such as respiratory deficiency due to paralysis of ventilatory muscles. This paper presents a fully configurable IC-centered stimulator designed to investigate muscle stimulation paradigms. It provides 8 current stimulation channels with high-voltage compliance and real-time operation capabilities, to enable a wide range of FES applications. The stimulator can be used in a standalone mode, or within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…By setting the PG-nFES with commonly used stimulation parameters for non-invasive neuromuscular applications and surface stimulation electrodes, upper limb movements of the hand and arm (involving the elbow and shoulder joints) were achieved (Figure 7). In contrast, many FPGA-based stimulation systems reported in the literature are targeted to invasive FES applications (Castelli et al, 2017) or are not aimed for upper limb applications (Chen et al, 2009). On the other hand, recent works reporting FES systems for the upper limb (De Marchis et al, 2016;Kutlu et al, 2016;Annetta et al, 2019;Torah et al, 2019;Ward et al, 2020), are designed for custom arrays of stimulation electrodes aimed to small muscles of the forearm to achieve wrist and finger movements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By setting the PG-nFES with commonly used stimulation parameters for non-invasive neuromuscular applications and surface stimulation electrodes, upper limb movements of the hand and arm (involving the elbow and shoulder joints) were achieved (Figure 7). In contrast, many FPGA-based stimulation systems reported in the literature are targeted to invasive FES applications (Castelli et al, 2017) or are not aimed for upper limb applications (Chen et al, 2009). On the other hand, recent works reporting FES systems for the upper limb (De Marchis et al, 2016;Kutlu et al, 2016;Annetta et al, 2019;Torah et al, 2019;Ward et al, 2020), are designed for custom arrays of stimulation electrodes aimed to small muscles of the forearm to achieve wrist and finger movements.…”
Section: Discussionmentioning
confidence: 99%
“…From the 1990s, FPGAs have been used to develop FES systems. They have been applied for Peripheral Nervous System (PNS) stimulation, like bladder (Sawan et al, 1996;Arabi and Sawan, 1999), respiration (Zbrzeski et al, 2016;Castelli et al, 2017), and visual prostheses (Wong et al, 2005). Also, they have been used for Central Nervous System (CNS) stimulation, including intracortical (Sugiura et al, 2016) and deep brain stimulation (Karami et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimed setups have been installed in multiple sites and are being used by partner laboratories in collaborative projects, always aiming for closed-loop experiments (BRAINBOW (EU project 284772, ICT- FET FP7/2007–2013, FET Young Explorers) [ 33 ], CENAVEX (ANR grant 2013-NEUC-0001-01 and NIH grant 5 R01 NS086088-02) [ 34 , 35 , 40 ], ISLET CHIP (ANR grant 2013-PRTS-0017) [ 25 , 41 ], HYRENE (ANR grant 2010-BLANC-0316-01) [ 21 ]). New needs in terms of processing capabilities arise from existing collaborations and can also emerge from new collaborations, leading to regular updates of the digital library.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested technology that can be used to synchronize artificial ventilation with intrinsic respiratory drive or to replicate its function. These methods include development of a controllable stimulator with an update frequency higher than the stimulation frequency and a real-time processing controller (Castelli et al, 2017), implementation of a bio-inspired spiking neural network model that follows intrinsic respiratory rate (Zbrzeski et al, 2016), predictive algorithms using body temperature and heart rate (Kimura et al, 1992), and breath-triggering through the use of genioglossus muscle activity (Mercier et al, 2017). However, these approaches have not yet been sufficiently developed or investigated.…”
Section: Controller Provided Autonomous and Individualized Ventilatormentioning
confidence: 99%